PELATIHAN MANAJEMEN DAN PEMASARAN BANDENG PDNA KOTA PROBOLINGGO - ana billah; Fia Ayuning Pertiwi; Ahmad Syaifudin Romli (LPPM STAI Muhammadiyah Probolinggo, 2024)
The health issues faced by communities are often caused by a lack of knowledge and awareness of healthy living practices. This study aims to enhance community awareness and participation through an education and empowerment-based service program. The methods employed include training, workshops, and outreach activities that involve active participation from the community. The results of the program indicate a significant increase in community knowledge and behavior regarding health issues, evidenced by the rising participation in health check-ups and the adoption of healthy practices in daily life. The implications of this research demonstrate that collaborative and participatory approaches are effective in empowering communities and supporting the sustainability of health programs. Additionally, these findings serve as a foundation for developing more relevant and responsive community service programs that address the evolving needs of society in the future. Keywords: Management, Marketing, Milkfish